BRIDGING THE GAP: EFFECTIVE TECHNIQUES FOR TEACHING ESL STUDENTS (Modern education and development, 2025)
This article discusses effective techniques for teaching English as a Second Language (ESL) students, focusing on methods that help overcome linguistic and cultural barriers. Techniques such as differentiated instruction, scaffolding, communicative language teaching (CLT), and the use of technology are explored. The article highlights how these strategies can be employed to improve ESL learners' language skills, increase their confidence, and ensure their integration into mainstream education. Drawing from various pedagogical sources, the article provides educators with practical approaches to meet the diverse needs of ESL students.